2009
DOI: 10.1111/j.1600-051x.2009.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical non‐surgical treatment of peri‐implantitis: a double‐blind randomized longitudinal clinical study. I: clinical results

Abstract: No group differences were found in the treatment outcomes. While plaque and bleeding scores improved, no effects on PPD were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
196
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(222 citation statements)
references
References 11 publications
11
196
1
9
Order By: Relevance
“…These findings are consistent with other studies. 34 The previous microbiological and clinical studies, demonstrated that mechanical debridement alone was not efficient for decontamination of implant surfaces and did not give rise to improvement of the clinical situation. 35 It is very difficult to eliminate bacteria from implant surfaces using mechanical methods alone.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with other studies. 34 The previous microbiological and clinical studies, demonstrated that mechanical debridement alone was not efficient for decontamination of implant surfaces and did not give rise to improvement of the clinical situation. 35 It is very difficult to eliminate bacteria from implant surfaces using mechanical methods alone.…”
Section: Discussionmentioning
confidence: 98%
“…Once a biofilm has become established on an implant surface, conventional methods of debridement are not effective for its removal [8]. An implant surface which is positioned below the position of the oral soft tissues cannot be reached with the bristles of a conventional toothbrush, as these only penetrate 0.5 mm into crevices around teeth and dental implants.…”
Section: Biofilm Development On Implant Surfacesmentioning
confidence: 99%
“…Traditional dental treatment modalities, such as the removal of biofilms using scaling instruments originally designed for debriding the roots of teeth to remove such deposits, cannot be applied in exactly the same way to threaded implant surfaces [8]. The implant surface structure has far more areas which are protected, and much of the surface is inaccessible to conventional professional instruments.…”
Section: The Complexities Of Biofilm Removal and Implant Debridementmentioning
confidence: 99%
“…Biofilms comprise of a grid of exopolysaccharides, proteins, and nucleic acids [9,14]. A considerable measure of infections in the oral hole, for example, caries, stomatitis, periodontal, and peri-embed maladies, are connected with biofilms [17]. Test and clinical reviews exhibited that peri-embed and periodontal tissues respond also to oral biofilms [2,6,12,16].…”
Section: Introductionmentioning
confidence: 99%